2021
DOI: 10.3389/fphys.2020.586921
|View full text |Cite
|
Sign up to set email alerts
|

Autoregulatory “Multitasking” at Endothelial Cell Junctions by Junction-Associated Intermittent Lamellipodia Controls Barrier Properties

Abstract: Vascular endothelial cell (EC) junctions are key structures controlling tissue homeostasis in physiology. In the last three decades, excellent studies have addressed many aspects of this complex and highly dynamic regulation, including cell signaling, remodeling processes of the proteins of tight junctions, adherens junctions, and gap junctions, the cytoskeleton, and post-transcriptional modifications, transcriptional activation, and gene silencing. In this dynamic process, vascular endothelial cadherin (VE-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…J3 and J4 are linear with J4 having continuous CDH5 signal distributed over a larger area than J3. J5 junctions are visually reminiscent of the reticular junctions previously described (Millán et al, 2010) but could also appear as transient structures (Kim and Cooper, 2018; Seebach et al, 2020). J0 junctions might result from mis-segmented cells therefore in downstream analyses we considered cells with less than 20% J0.…”
Section: Resultsmentioning
confidence: 67%
“…J3 and J4 are linear with J4 having continuous CDH5 signal distributed over a larger area than J3. J5 junctions are visually reminiscent of the reticular junctions previously described (Millán et al, 2010) but could also appear as transient structures (Kim and Cooper, 2018; Seebach et al, 2020). J0 junctions might result from mis-segmented cells therefore in downstream analyses we considered cells with less than 20% J0.…”
Section: Resultsmentioning
confidence: 67%
“…Immunostaining and live imaging of EC monolayers has highlighted differences in cell morphology and junction patterns in response to stimuli or under distinct cell culture conditions (Abu Taha et al, 2014;Lampugnani et al, 1992;Seebach et al, 2016;Vestweber et al, 2009). We focussed on analysing proliferation, junctions, and NOTCH activation.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies on EC junction (Brezovjakova et al, 2019;Seebach et al, 2015;Wiseman et al, 2019) did not analyse the proportion of different junction pattern; our method classifies whole junctions' objects using an expert-trained ML algorithm (CPA with Fast Gentle Boosting, Appendix 1). In line with the literature in the field (Seebach et al, 2016), we classified junctions in a scale from 0 to 5 (Figure 5A). J0, J1 and J2 are discontinuous, highly jagged, or jagged junctions respectively.…”
Section: Analysis Of Junction Heterogeneitymentioning
confidence: 85%
See 1 more Smart Citation
“…VE-cadherin also generates a dynamic balance between endothelial cell growth and perictyte coverage in blood vessels and helps maintain blood vessel homeostasis. Also, VE-cadherin regulates the growth rate of vascular endothelial cells by regulating angiogenic factors ( 37 , 38 ). Studies have shown that VE-cadherin knockout mice experience difficulties forming initial continuous blood vessels due to adhesion barriers between endothelial cells, causing death within 10 days of embryonic development ( 39 ).…”
Section: Discussionmentioning
confidence: 99%